Screening of Kidney Disease in Asymptomatic Female College Students by Urine Dipstick Method - Chhetri, Santosh; Shah, Dibya S (Journal of Institute of Medicine Nepal, 2019)
Introduction: Urine examination by urine dipstick method is a useful tool to identify asymptomatic individual for kidney disease. A urine dipstick analysis was conducted on world kidney day to determine the urine abnormalities among asymptomatic female college students.Methods: A cross-sectional study was carried out in a government female college in Kathmandu Nepal. Three hundred asymptomatic female students participated in this study. Fresh midstream urine samples were obtained and tested by urine dipstick method. Random Blood glucose was monitored with glucometer. Blood pressure was measured by manual sphynomanometer.Results: The mean age of the female students was 22.62±2.686 years. Fifteen participants (5%) were found positive for proteinuria and only 1% of participants had glycosuria. The systolic blood pressure of >120 mm Hg was present in 14% of participants while 5% of participants had diastolic blood pressure of >90mm Hg. Participants who were found to have urinary proteinuria detected had both systolic and diastolic blood pressure increased. Only 8% of the participants had random blood sugar of >140 mg/dl.Conclusion: Urinary abnormalities like proteinuria and glycosuria in asymptomatic female students has significant prevalence. Systemic prehypertension and hypertension has alarming rates among adolescents. Hence, screening for blood pressure and early detection of renal disorders will lead to effective interventions and possibly reduce the burden of renal diseases.